Evaluación de la saturación promedio de los fluidos del “pozo A” con los datos obtenidos de la herramienta RST, en el área sur del Campo Castilla (2018)
The present work is developed with the purpose of evaluating the average saturation of the fluids by means of the interpretation of the data taken with the RST log, for the A well of Campo Castilla, which is in production by the company Ecopetrol S.A. To achieve the objective set out above, the interpretation of the runs performed with open-hole log (spontaneous potential, gamma ray, resistivity, neutron and density) and cased hole (RST) is performed, determining the potential areas of interest in the well A, located in the Gacheta and Une Formations. The calculation is made from the logs in the determination of the petrophysical properties such as: porosity, permeability, water saturation and oil saturation, using mathematical models; analyzing the results, the Netres and Netpay zones are determined, and possible areas of cannonade are compared and determined. The interpretation of the logs show the benefits that the implementation of the RST tool provides in the determination of the petrophysical properties of a piped well, since it provides accurate and reliable information of the acquired data.